Kesenjangan Tata Kelola dan Kinerja Lingkungan yang Belum Merata: Analisis Perencanaan Lingkungan Strategis dan Tata Kelola Lingkungan yang Baik di Kota Tanjungpinang - Zuleriwati A.S; Hoki Apriyenson; Nefriwati Hilmi; Dea Rizky Saputri; Arie Afriadi; Aria Bagiasa Chidmahdjati; M . Ari Fandi (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2026)
This research analyzes the correlation between strategic environmental planning and actual environmental performance in Tanjungpinang City in 2017–2023, focusing on the role of good environmental governance (GEG). Unlike previous studies that consider environmental indicators or governance separately, this study bridges the gap by combining performance evaluation and governance analysis into one framework. This evaluative case study combines descriptive quantitative analysis with qualitative document analysis. Secondary data from official planning documents and institutional reports were analyzed through gap and trend analyses, complemented by a qualitative assessment of governance principles. Only three indicators exceeded their established targets—the Water Quality Index, the Percentage of Regional Climate Change Action Plan, and the Environmental Quality Index—while the Environmental Data and Information indicator met its target exactly; the Land Cover Quality Index and waste-related indicators performed relatively weakly. This uneven pattern shows that meeting targets does not guarantee consistently good environmental performance. The trend analysis reveals generally stable gains across most variables, alongside persistent shortcomings in land use management. Environmental performance appears strongly influenced by governance quality, particularly policy coordination and integration: indicators under tighter administrative control perform better, while those requiring cross-sectoral cooperation perform worse. This paper thus contributes to understanding that environmental-planning effectiveness depends not only on target achievement but also on governance's capacity to translate policy into coordinated cross-sectoral action. Strengthening cross-sectoral integration, accountability, and participatory mechanisms is essential to achieving more aligned and sustainable environmental outcomes.